KONFLIK KERJA-KELUARGA PADA ISTRI YANG BEKERJA & MENJALANI LONG DISTANCE MARRIAGE - Nanda Rossalia; Dwi Larasati; Mohammad Adi Ganjar Priadi (MANASA, 2020)
Every woman has a chance to work in any kind of job with any responsibilities, such as workingout of their domicile. For working wives, the differences between a husband’s and a wife’s rolesin the family make the working wive face a lot of conflicts due to their dual role as a worker anda homemaker. It also give effort of every women to make their life steady, even if they have multirole in their families. This can affect marriage satisfaction that it needs a good conflictmanagement to resolve the work-family conflict. This research aims to see the overview of workfamily conflict for wives who are working out of their domicile. This research is using qualitativemethod with semi-structure interview. Participants are wives who are working out of theirdomicile, as a vocal instructure (35), flight attendant (27), and geologist (44), having children anda working husband. Results show that all three participants have had different types of conflict ina various context and experience. Participants experienced job spouse conflict, job parent conflict,and job homemaker conflict. Future research should put focus on related variable with work familyconflict, such as age of marriage, conflict management, and so on.